Golden Generation Generator. Visualización, reproducción y clausura de sesgos estructurales en la producción arquitectónica reciente en Chile, a través del aprendizaje maquínico - Portal Carrasco, Fernando Andrés. (Pontificia Universidad Católica de Chile, 2022)
Deconstruction questions not only the solidity of structures to detect their weakest points but also whether what we understand by structure is actually structural. If we ask, for example, what is structural in a tradition? we can observe – as this research does – that the structure is based on the reiteration of images. But when processing this repetition ad infinitum with artificial intelligence tools, the structural failure appears: an architectural image as disturbing as those that evoke deconstruction.
Golden generation generator: visualization, reproduction, and closure of structural biases in recent architectural production in Chile, through machine learning
Keywords: Arquitectura